Sexology in Portugal: Narratives by Portuguese Sexologists - Alarcão, Violeta (2022)
This article presents the emergence and development of modern sexology in Portugal through the analysis of Portuguese sexologists’ narratives, to explore how they commit to a professional identity as sexologists, and to discuss how they integrate their professional role into the vast multidisciplinary field of sexology. In-depth interviews were conducted with 44 key profes sionals, purposefully recruited to uarantee heterogeneity concerning generation, gender, train ing, and practice. Content analysis focused on highlighting differences and articulations among the main professionals making up the field. The findings indicate that sexology is not seen as a full-fledged profession but rather as a specialization or a secondary field of action. The sexual medicine perspective is prevalent and more visible among physicians, thus reflecting the gap between psychosocial and biomedical approaches. A close link between clinical work and research and a gap between clinical work and health promotion were found. Despite the multidisciplinary nature of sexology being acknowledged, it is not fully implemented by the experts in the field. However, it is this characteristic that permitted sexology to institutionalize and to legitimate itself as a discourse of truth about sex, in Portugal as in other countries.